Collective Memory and Baltic States: From the Baltic Way to the Age of Hybrid Threats - Celso Cancela Outeda (Pasado y Memoria, 2025)
This article examines the evolution of collective memory and historical narratives in the Baltic states, adopting a diachronic perspective to trace their trajectory from the Soviet era to the present. The Baltic Way, a central moment of anti-Soviet resistance, played a central role in shaping a distinct ethno-national identity, challenging Soviet narrative and fostering national unity. Following EU accession (2004), the Baltic states leveraged their membership to promote these narratives at the European level, influencing memory politics and relations with Russia. However, since 2014, geopolitical shifts –particularly Russia’s annexation of Crimea and the invasion of Ukraine (2022)– have intensified contestation over historical narratives, even leading to a discernible «de-Europeanisation» of collective memory. This process has been exacerbated by the rise of populist movements and the instrumentalization of memory within hybrid threats, including disinformation campaigns. The securitisation of narratives, driven by Russian interference, has replaced earlier emphases on European values with national security concerns. This shift fuels exclusivist narratives, often exploited to mobilise support, exacerbating nationalism and xenophobia. Consequently, collective memory has become a battleground in international relations, with significant implications for democratic resilience, European stability, and international order. This study analyses these dynamics, revealing how historical narratives are strategically repurposed to legitimise political agendas and discredit opposition.